2023
DOI: 10.3389/fimmu.2023.1111777
|View full text |Cite
|
Sign up to set email alerts
|

Advances in CRISPR/Cas gene therapy for inborn errors of immunity

Abstract: Inborn errors of immunity (IEIs) are a group of inherited disorders caused by mutations in the protein-coding genes involved in innate and/or adaptive immunity. Hematopoietic stem cell transplantation (HSCT) is a mainstay definitive therapy for many severe IEIs. However, the lack of HLA-matched donors increases the risk of developing severe immunological complications. Gene therapy provides long-term clinical benefits and could be an attractive therapeutic strategy for IEIs. In this review, we describe the dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 253 publications
0
8
0
Order By: Relevance
“…Also, there is a variety of treatment options for the management of immune dysregulation in IEIs depending on the specific type, severity, and pathway involved in the disorder. These include systemic immunosuppressants, enzyme replacement therapy, small molecules, biological therapies (such as monoclonal antibodies), and adoptive cell therapies (ACT) such as hematopoietic stem cell transplantation (HSCT), gene therapy ( 54 , 118 , 119 ) and, in the near future, cell-based therapies. The aim of this review is to ascertain available Treg cell-based therapies more comprehensively and, as such, the other therapies will be briefly summarized.…”
Section: Treg Cell-based Therapiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, there is a variety of treatment options for the management of immune dysregulation in IEIs depending on the specific type, severity, and pathway involved in the disorder. These include systemic immunosuppressants, enzyme replacement therapy, small molecules, biological therapies (such as monoclonal antibodies), and adoptive cell therapies (ACT) such as hematopoietic stem cell transplantation (HSCT), gene therapy ( 54 , 118 , 119 ) and, in the near future, cell-based therapies. The aim of this review is to ascertain available Treg cell-based therapies more comprehensively and, as such, the other therapies will be briefly summarized.…”
Section: Treg Cell-based Therapiesmentioning
confidence: 99%
“…This strategy entails the modification of HSC and other immune cells involved in the disease process. Subsequent to its inception, significant advances have been made such as using self-inactivating lentiviruses, rendering this approach a promising and safer alternative compared to its earlier iterations ( 119 , 120 ). Indeed, in 2016, Strimvelis™ was approved in Europe for the treatment for ADA-SCID.…”
Section: Treg Cell-based Therapiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Further human trials involving CRISPR are currently underway, with the tool having shown particular promise in the treatment of numerous conditions, including certain cancers. However, this research is the first published that involves CRISPR’s use directly inside the body [ 33 ]; almost all of the other studies performed genome editing in extracted cells, which were then reintroduced. A treatment for restoring sight by injecting CRISPR into a patient’s eye has also emerged, but it has not yet been the subject of any scientific publication.…”
Section: Crispr-cas9 Clinical Trials and Therapeutic Usementioning
confidence: 99%
“…Here, English and New Zealand teams, in association with the Intellia Therapeutics and Regeneron Pharmaceuticals laboratories, directly injected CRISPR into the blood of people suffering from transthyretin amyloidosis, an inherited disease characterized by attacks on the nervous system, kidneys, and heart. This rare pathology is characterized by a mutation in the TTR gene, which leads to the accumulation of transthyretin proteins in deposits around nerves and organs [ 31 , 33 ].…”
Section: Crispr-cas9 Clinical Trials and Therapeutic Usementioning
confidence: 99%